The Role of Intellectual Capital and Knowledge Management in Enhancing FMCG Firm Performance - Aburizal Maharsyah (Universitas Mercu Buana, 2026)
Researchaims:ThisstudyaimstoanalyzetheroleofIntellectualCapital(IC) and Knowledge Management (KM) in influencing Firm Performance (FP) in companies within the Fast-Moving Consumer Goods (FMCG) sector.Design/Methodology/Approach: A quantitative approach was employed using thePartialLeastSquaresStructuralEquationModeling(PLS-SEM)method.Data werecollectedthroughquestionnairesdistributedto104respondentsacrossvarious job levels.Research findings: The results indicate that both IC and KM have a positive and significant impact on FP.Furthermore, KM was foundto partially mediate therelationship between IC and FP, implying that a firm’s success is not only determinedbyintellectualcapitalbutalsobyitsabilitytomanageandutilizeknowledge effectively.Theoretical Contribution/Originality: This study contributes to the developmentofICandKMliteraturebyhighlightingthemediatingroleofKMinenhancing firm performance, particularly in the FMCG sector.Practitioners/Policy Implications: The findings provide practical insights for managersindesigningandimplementingknowledge-basedstrategiesthatintegrate IC and KM to strengthen firm performance and build sustainable competitive advantage in dynamic markets.ResearchLimitations/Implications:Thestudyislimitedbyitssamplesizeand focus on the FMCG sector. Future research may expand to other industries and employ longitudinal data to capture performance dynamics over time.